MOOD AND EMPATHY ON PROSOCIAL BEHAVIOUR AMONG MUSLIM ADOLESCENTS IN PADANG CITY - Aziz Sinaga, Malim Abdul; Netrawati, Netrawati; Neviyarni, Neviyarni; Hariko, Rezki; Pertiwi, Yuarini Wahyu (Psikis : Jurnal Psikologi Islami, 2023)
This research is motivated by the phenomenon at the Dharmabakti Nusantara Health Vocational School in Padang City; mood and empathy are thought to influence prosocial behaviour. This study aims to analyse: 1) mood, empathy and prosocial behaviour, 2) the relationship between mood and prosocial behaviour, 3) the relationship between empathy and prosocial behaviour, and 4) the relationship between mood and empathy together with prosocial behaviour. The method used in this study is a Quantitative method that aims to determine the relationship and influence between variables. The research sample was taken from the existing population of 80 students. The research instrument used a questionnaire with a Likert scale model. The data were analysed with descriptive statistics, simple regression, and multiple regression; the results of the research data analysis obtained an R-value of 0.558 with a p level = 0.000 (p <0.05). There is a significant relationship between mood and empathy with prosocial behaviour. R2 =0,311 %. This study proves a positive and meaningful relationship between philosophy and heart in prosocial behaviour at SMK Dharmabakti Nusantara Pota Padang.